Sustainability Practices As A Competitive Edge In Five Star Hotels Of Delhi: A Study on Managerâs Perception - Mathur, Shweta; Khanna, Kavita (International Research Journal of Management, IT & Social Sciences, 2017)
The study aims to conduct an analysis describing the sustainable strategy available for hotels, evaluating its potential to create competitive advantage and exploring how its implementation influences other actors in the industry specifically and the whole area development generally. For the purpose of this study Delhi has been chosen with focus on the Five star and Five star Deluxe Hotels of the city. A survey was conducted with the employees working in 15 Five star and Five star Deluxe Hotels in Delhi. According to the analysis, the sustainable efforts of the hotel include environmental, social and economic initiatives. The results of the survey highlighted the sustainability practices that are being adopted and the extent of their implementation by these hotels. It also showed the relationship between hotelâs sustainability practices and employeesâ satisfaction. Furthermore, the study has explored the ability of sustainable efforts to create unique reputation for the hotel which may enable it to gain competitive edge. The latter, in turn, attracts the business customers who consider sustainable hotel as valuable partner for their own reputation. All in all, as the sustainability practices enhance the profitability, it is considered a source of completive advantage.